Water Communication : Analysis of Strategies and Campaigns from the Water Sector - Herve-Bazin, Celine (IWA Publishing, 2014)
"The book facilitates coordination within the water sector and its organizations as water is a wide field of applications where inadequate words and language undrestatnding between its stakeholders is one of the main obstacles today ..."--Back cover